Dampak Promosi dan Harga Terhadap Keputusan Pembelian Paket Haji dan Umrah PT Al Ikhlas Wisata Mandiri, 2019 - Ahmad, Widad (Study of Scientific and Behavioral Management, 2020)
Along with the increase in Indonesia’s economic capacity, the number of Indonesian pilgrims from time to time has increased. The high waiting list for pilgrims from Indonesia has prompted the Ministry of Religion (Kemenag) to plan to socialize the obligation to perform the haj pilgrimage once in a lifetime. This study aims to determine the impact of promotions and prices on purchasing decisions on Hajj and Umrah packages. This research is a quantitative study with an analytic survey approach with a cross-sectional study method. The results of this study are Price has no effect on purchasing decisions, while Promotion has an effect on customer satisfaction. Kata Kunci : Price, Promotion, dan Purchasing Decisions Hajj and Umrah packages